2010
DOI: 10.1093/annonc/mdp520
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre phase II gene expression profiling study of putative relationships between tumour biomarkers and clinical response with erlotinib in non-small-cell lung cancer

Abstract: Background: Identification of appropriate markers for predicting clinical benefit with erlotinib in non-small-cell lung cancer (NSCLC) may be able to guide patient selection for treatment. This open-label, multicentre, phase II trial aimed to identify genes with potential use as biomarkers for clinical benefit from erlotinib therapy.Methods: Adults with stage IIIb/IV NSCLC in whom one or more chemotherapy regimen had failed were treated with erlotinib (150 mg/day). Tumour biopsies were analysed using gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…EMT will be more relevant for invasive tumor growth in vivo, and clinical studies have already shown the link between E-cadherin (CDH1) levels and response to erlotinib (12). The retrospective analysis presented here on data from the MERIT trial confirms that patients with higher expression of E-cadherin (CDH1) have an increased clinical benefit from treatment with erlotinib, as previously published (18). A similar analysis has been conducted on gefitinib by Kook and colleagues and did not show any correlation of E-cadherin expression with response rate or with progression-free survival and overall survival in patients with inoperable stage IIIB/IV NSCLC treated with gefitinib (37).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…EMT will be more relevant for invasive tumor growth in vivo, and clinical studies have already shown the link between E-cadherin (CDH1) levels and response to erlotinib (12). The retrospective analysis presented here on data from the MERIT trial confirms that patients with higher expression of E-cadherin (CDH1) have an increased clinical benefit from treatment with erlotinib, as previously published (18). A similar analysis has been conducted on gefitinib by Kook and colleagues and did not show any correlation of E-cadherin expression with response rate or with progression-free survival and overall survival in patients with inoperable stage IIIB/IV NSCLC treated with gefitinib (37).…”
Section: Discussionsupporting
confidence: 81%
“…The next steps were to investigate a potential structural explanation for this binding discrepancy between the 2 compounds, as well as using an EMT-inducible cellular model to assess their respective functional effect on EMT. These findings were further correlated with gene expression data from the MERIT open-label, multicenter, phase II clinical trial, which aimed to identify genes with potential as biomarkers for clinical benefit from erlotinib therapy (18).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Many studies have identified activating EGFR gene mutations in only a small number of cases in PDAC patients (33,34). However, Tan et al demonstrated that higher genetic amplification of the EGFR region of chromosome 7 is associated with better clinical responses to erlotinib treatment in advanced NSCLC patients (35). Therefore, there is a possibility that quantitative analysis of EGFR mRNA expression levels could be helpful in predicting sensitivity to erlotinib in PDAC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as showed in the TRIBUNE phase Ⅲ trial, it was first studied in United States, Asia and Europe, but did not have consistent results following approval by the US Food and Drug Administration (FDA) and European Medicine Agency (EMEA) in firstline chemotherapy patients [27,30,61,62,68] . The genetic mutation of EGFR in exons 19 and 21 of chromosome 7 demonstrated an association with response to erlotinib [40,68] . Therefore, erlotinib is approved for the treatment of patients with refractory disease.…”
mentioning
confidence: 99%